Senior High School Students’ Anxiety to Speak English at One Senior High School in Jambi City - Maimunah Maimunah (Institute of Information Technology and Social Science (IITSS), 2021)
This study is intended to fill the gap in the literature on Indonesian senior high schools students’ anxiety. This study was to investigate the senior high school student’s anxiety to speak English. This research was conducted by using a qualitative design with a case study approach to investigate the senior high school student’s anxiety to speak English. There were ten participants in this study and all of participants come from the same class. The demographic data were analyzed descriptively in which every participant’s information was described. Then, the interviewed data were transcribed into the researcher’s computer and the researcher had to translate it into English. Based on the interview data analysis, there were five themes that were related to the causes of students’ anxiety to speak English inside and outside the classroom. the researcher concludes that the causes of students’ anxiety to speak English inside and outside the classroom of the eleventh grade at one senior high school in Jambi are (1) low speaking skill, (2) fear of negative responses from others, (3) low self-esteem to speak English, (4) fear of failure to speak English with teachers, and (5) cultural influences to speak English due to more teacher-centered.